2018
DOI: 10.1155/2018/3691468
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Distribution Laws of Drilling Force for Staggered Teeth BTA Deep Hole Drill

Abstract: The boring and trepanning association (BTA) deep hole drilling is a typical self-guiding machining method. The drilling force and its distribution laws along the cutting radius directly affect the stability of drilling and the quality of machined hole. Based on the oblique cutting theory, a novel drilling force model is developed to predict the thrust and torque for staggered teeth BTA deep hole drill with variable geometries. Using the constraint relationships between the cutting force components and cutting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It is known that the initial mass of the human tooth is between 0.51 grams and 2.28 grams [19] and the mass depends on many factors: oldness of the person, type of the tooth, depth of the root etc. The drill diameter is in the interval 1-5 mm, the drilling velocity is in the interval of 13-15 m/min and the suggested feed rate for tooth drilling is 0.005-0.06 mm/rev [7]. Assuming the numerical data D=2 mm, fr= 0.05 mm/rev, m0=1.32 g, v=15 m/min, the mass variation is = 1.32 − 0.002 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the initial mass of the human tooth is between 0.51 grams and 2.28 grams [19] and the mass depends on many factors: oldness of the person, type of the tooth, depth of the root etc. The drill diameter is in the interval 1-5 mm, the drilling velocity is in the interval of 13-15 m/min and the suggested feed rate for tooth drilling is 0.005-0.06 mm/rev [7]. Assuming the numerical data D=2 mm, fr= 0.05 mm/rev, m0=1.32 g, v=15 m/min, the mass variation is = 1.32 − 0.002 .…”
Section: Discussionmentioning
confidence: 99%
“…Diameter of the hole and feed rate determine the drilling force. Distribution of the measured drilling force along the cutting radius is presented in [7]. It is concluded that the force directly affect the stability of the operation and the quality of machined hole.…”
Section: Introductionmentioning
confidence: 99%
“…The geometric parameters of the BTA drill have an important influence on deep-hole drilling; the geometric parameters of the BTA drill are selected as follows. The value of rake angle of the BTA drill depends on the material property and processing requirements [34]. Due to the small plastic deformation and high chemical activity of TA10, the contact length between the rake face and the chip is small, the cutting stress and cutting temperature are relatively concentrated, and the hardened layer is easily produced on the rake face; so, a smaller rake angle should be used to strengthen the edge strength and increase the contact area between the chip and the rake face.…”
Section: Structure Of the Toolmentioning
confidence: 99%
“…BTA drilling is one of primary machining types which are used to produce deep holes (Yang et al , 2018; Li et al , 2019). BTA stands for Boring and Trepanning Association (Thil et al , 2013), and Figure 1 from Sandvik Coromant shows BTA drilling (Li et al , 2020; Li et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…BTA drilling is one of primary machining types which are used to produce deep holes (Yang et al , 2018; Li et al , 2019). BTA stands for Boring and Trepanning Association (Thil et al , 2013), and Figure 1 from Sandvik Coromant shows BTA drilling (Li et al , 2020; Li et al , 2019). The BTA drilling tool is threaded onto the drill tube (Yu, 2016); and the coolant(oil) indicated by arrows in Figure 1 flows through the gap between the deep hole and the drill tube to the drilling tool, then drives chips past the hole in the drilling tool and drill tube to the right box and the coolant tank (Figure 1) (Ma and Shen, 2018a, 2018b, 2017).…”
Section: Introductionmentioning
confidence: 99%